Efektivitas Model Pembelajaran Discovery Learning dan PBL terhadap Kemampuan Berpikir Kritis Siswa - Tri Julia Sari Aritonang; Suhandi Astuti (Musamus Journal of Primary Education, 2021)
This study aims to determine the effectiveness of the learning model Discovery Learning and Problem Based Learning in terms of the critical thinking skills of grade V elementary school students. This type of research is a meta analyst. The data analysis technique used is the Effect size analysis technique. The effect size formula is the effect formula with the eta squared (ή2) formula. The instrument used in this study was a coding sheet. The variables used to obtain coding information on the effect size of the meta-analysis study. The results showed that the Discovery Learning learning model was more effective than the Problem Based Learning learning model for improving students' critical thinking skills. Ancova test results show f count> f table of 0.009 and F count obtained is 6.12, namely 6.12> 0.65 and a significance of 0.001 <0.05 which indicates that there is an effectiveness of Discovery Learning and Problem Based Learning learning models in improving critical thinking skills of class students V SD.